Professionalization Contracts for Small Municipal Water Service Providers in India : Business Model Development - Ehrhardt, David (World Bank, Washington, DC, 2015)
Professionalization contracts are a new concept. The aim of these contracts is to enlist the support of specialized private firms in turning public water utilities into competent professional operators. This report looks at how the business model for such contracts may work. This report builds on fieldwork and consultation in India. The model described in this report reflects two weeks of meetings with water sector stakeholder in India, including a workshop held at the World Bank country office in Delhi on 22 March 2011. The report gives introduction in section one. It describes briefly the need for professionalization contracts in India, and the target market section two. It then summarizes what the contractor will do, and how this differs from traditional capacity building, as well as from traditional public private partnership (PPP) concepts such as management contracts section three. The report then describes the complementary policy and institutional reforms that will be needed at the state and local government levels to make professionalization contracts successful section four. Section five looks at the political economy of professionalization contracts, identifying risks, and how these risks can be mitigated through design of the institutional reforms and the business model. Section six then turns to the true business model aspects by describing indicative costs of the professionalization contract and the complementary investments required. Section seven considers what the sources of funding for these costs would be, and section eight goes on to explain how the contractor will be paid, and hence the incentives under which it will operate. Section nine looks at the market of potential contractors, and examines their incentives to participate. Finally, section ten sets out some considerations for developing the concept.